2018
DOI: 10.1002/14651858.cd012410.pub2
|View full text |Cite
|
Sign up to set email alerts
|

L-ornithine L-aspartate for prevention and treatment of hepatic encephalopathy in people with cirrhosis

Abstract: The results of this review suggest a possible beneficial effect of L-ornithine L-aspartate on mortality, hepatic encephalopathy, and serious adverse events in comparisons with placebo or no-intervention, but, because the quality of the evidence is very low, we are very uncertain about these findings. There was very low quality evidence of a possible beneficial effect of L-ornithine L-aspartate on hepatic encephalopathy, when compared with probiotics, but no other benefits were demonstrated in comparison with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 100 publications
3
65
0
7
Order By: Relevance
“…Although there was a significant reduction in ammonia in the drug arm, no differences in survival were observed, possibly because of the relatively low sample size. In a meta‐analysis of L‐ornithine L‐aspartate for prevention and treatment of HE that included 1,489 patients, L‐ornithine L‐aspartate administration was associated with a relative reduction in mortality compared to placebo (relative risk, 0.42; 0.24‐0.72), suggesting that ammonia lowering may improve survival of patients with cirrhosis with AD . The data showing that an increase in ammonia levels between day 5 and admission was associated with an increased risk of death and with worsening of HE provide support for the argument that ammonia should be a therapeutic target.…”
Section: Discussionmentioning
confidence: 86%
“…Although there was a significant reduction in ammonia in the drug arm, no differences in survival were observed, possibly because of the relatively low sample size. In a meta‐analysis of L‐ornithine L‐aspartate for prevention and treatment of HE that included 1,489 patients, L‐ornithine L‐aspartate administration was associated with a relative reduction in mortality compared to placebo (relative risk, 0.42; 0.24‐0.72), suggesting that ammonia lowering may improve survival of patients with cirrhosis with AD . The data showing that an increase in ammonia levels between day 5 and admission was associated with an increased risk of death and with worsening of HE provide support for the argument that ammonia should be a therapeutic target.…”
Section: Discussionmentioning
confidence: 86%
“…In contrast, Alvares-da-Silva et al reported no significant differences between oral LOLA administration (for 60 days) and placebo in the mental state and neuropsychological tests in MHE patients [99], but the therapy was useful in preventing further episodes of OHE. In summary, the administration of LOLA has shown improvement in the mental state and a decrease in the blood ammonia concentration in LC patients with OHE or CHE [100,101]. However, further studies considering the degree of hepatocellular damage and the stage of HE are necessary.…”
Section: Other Ammonia-lowering Drugsmentioning
confidence: 87%
“…The treatment by LOLA (in oral and intravenous forms) for covert HE and HE has been recently developed in European countries, although it is not available in the United States and Japan. In clinical trials, intravenous administration of LOLA showed a significant effect by reducing HE grade, decreasing venous blood ammonia concentration, and improving psychomotor function in patients with MHE and OHE compared to placebo [97][98][99][100]. A large scale study by Sidhu et al reported that five days of intravenous LOLA (30 g daily), as an add-on therapy with lactulose (30-120 mL through a nasogastric tube or orally and/or lactulose enema) and ceftriaxone (2 g twice daily), can significantly improve the grade of HE over days 1-4, but not on day 5 compared to placebo [98].…”
Section: Other Ammonia-lowering Drugsmentioning
confidence: 99%
“…However, the use of LOLA for the prevention/prophylaxis of OHE in cirrhosis has not, to date, been a major source of concern and there are no published reports of systematic reviews/meta-analyses of trials dedicated to the efficacy of LOLA for OHE prevention. Sporadic reports are limited in number to small sub-groups of very low numbers of trials and patients but results so far are inconsistent (Goh et al 2018;Thumburu et al 2017). Given this paucity of available data and as a basis for planned research in this area, the present systematic review with meta-analysis was undertaken in order to review the evidence base in support of a beneficial effect of LOLA for OHE prevention/prophylaxis in patients with cirrhosis.…”
Section: Introductionmentioning
confidence: 99%